HUKUM DAN PERAN LILIFUK DI TENGAH REZIM PEMERINTAHAN: ANALISIS HUKUM DAN KEBERLANJUTAN KEARIFAN LOKAL DI DESA KUANHEUN, KABUPATEN KUPANG BARAT, NUSA TENGGARA TIMUR - Asagabaldan, Meezan Ardhanu (Fakultas Ilmu Budaya Universitas Diponegoro, 2017)
The main objective of the management of coastal areas and marine resources is preserving resources and improving the welfare in coastal areas and small islands. The Ecological, social and cultural rights of local communities are the foundation for management of sustainable resource. Lilifuk is one of the local wisdoms in, West Kupang, with the aim is to support the conservation of coastal and marine. The main income of Lilifuk is fish catch such as lada/Beronang (Siganus spp.), Alu-alu/barracuda (Sphyranidae), grouper (Ephinephelus), and Peperek (Leigonathidae). Lilifuk has some beneficial thing for economical, social, and environmental aspects. Local communities that are involved, either directly or indirectly, make a significant contribution in keeping the existence of Lilifuk.